An ethnobotanical survey of wild edible plants of Paphos and Larnaca countryside of Cyprus - Paraskeva-Hadjichambi Demetra; Della Athena; Hadjichambis Andreas Ch (BMC, 2006)
Abstract An ethnobotanical survey of wild edible plants of Cyprus was carried out in two sites. Paphos vine zone and Larnaca mixed farming zone. These are among the areas in Cyprus whose inhabitants subsisted primarily on pastoralism and agriculture and therefore still preserve the traditional knowledge on wild edible plants. The information was collected for three-year period, in the framework of the EU-funded RUBIA Project. Four hundred and thirteen interviews have been administered to 89 informants of various ages and background categories in 29 villages of Paphos site, and 8 in Larnaca site. A total of 78 species were recorded. Ethnographic data related to vernacular names, traditional tools and recipes have also been recorded. A comparison of the data collected from the two sites is undertaken. During this ethnobotanical research it was verified that wild edibles play an important role in Cyprus in rural people, however, it was realized that the transmission of folk uses of plants decreased in the last generations. The research of ethnobotany should be extended to other areas of Cyprus in order not only to preserve the traditional knowledge related to plants but to make it available to future generations as well.